Theoretical and experimental investigations of mercury adsorption on hematite surfaces. (2nd January 2018) - Jung, Ji-Eun; Liguori, Simona; Jew, Adam D.; Brown, Gordon E.; Wilcox, Jennifer
ABSTRACT: One of the biggest environmental concerns caused by coal-fired power plants is the emission of mercury (Hg), which is toxic metal. To control the emission of Hg from coal-derived flue gas, it is important to understand the behavior and speciation of Hg as well as the interaction between Hg and solid materials in the flue gas stream. In this study, atomic-scale theoretical investigations using density functional theory (DFT) were carried out in conjunction with laboratory-scale experimental studies to investigate the adsorption behavior of Hg on hematite (α-Fe2 O3 ). According to the DFT simulation, the adsorption energy calculation proposes that Hg physisorbs to the α-Fe2 O3 (0001) surface with an adsorption energy of −0.278 eV, and the subsequent Bader charge analysis confirms that Hg is slightly oxidized. In addition, Cl introduced to the Hg-adsorbed surface strengthens the Hg stability on the α-Fe2 O3 (0001) surface, as evidenced by a shortened Hg-surface equilibrium distance. The projected density of states (PDOS) analysis also suggests that Cl enhances the chemical bonding between the surface and the adsorbate, thereby increasing the adsorption strength. In summary, α-Fe2 O3 has the ability to adsorb and oxidize Hg, and this reactivity is enhanced in the presence of Cl. For the laboratory-scale experiments, three types of α-Fe2 O3 nanoparticles were prepared using the precursors Fe(NO3 )3, Fe(ClO4 )3, and FeCl3, respectively. The particle shapes varied from diamond to irregular stepped and subrounded, and particle size ranged from 20 to 500 nm depending on the precursor used. The nanoparticles had the highest surface area (84.5 m 2 /g) due to their highly stepped surface morphology. Packed-bed reactor Hg exposure experiments resulted in this nanoparticles adsorbing more than 300 μg Hg/g. The Hg LIII -edge extended X-ray absorption fine structure spectroscopy also indicated that HgCl2 physisorbed onto the α-Fe2 O3 nanoparticles. Implications : Atomic-scale theoretical simulations proposes that Hg physisorbs to the α-Fe2 O3 (0001) surface with an adsorption energy of −0.278 eV, and the subsequent Bader charge analysis confirms that Hg is slightly oxidized. In addition, Cl introduced to the Hg-adsorbed surface strengthens the Hg stability on the α-Fe2 O3 (0001) surface, as evidenced by a shortened Hg-surface equilibrium distance. The PDOS analysis also suggests that Cl enhances the chemical bonding between the surface and the adsorbate, thereby increasing the adsorption strength. Following laboratory-scale experiment of Hg sorption also shows that HgCl2 physisorbs onto α-Fe2 O3 nanoparticles which have highly stepped structure.